2013
DOI: 10.1093/nar/gkt847
|View full text |Cite
|
Sign up to set email alerts
|

Type I restriction enzymes and their relatives

Abstract: Type I restriction enzymes (REases) are large pentameric proteins with separate restriction (R), methylation (M) and DNA sequence-recognition (S) subunits. They were the first REases to be discovered and purified, but unlike the enormously useful Type II REases, they have yet to find a place in the enzymatic toolbox of molecular biologists. Type I enzymes have been difficult to characterize, but this is changing as genome analysis reveals their genes, and methylome analysis reveals their recognition sequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
255
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(259 citation statements)
references
References 239 publications
(260 reference statements)
4
255
0
Order By: Relevance
“…The basic modification complex, HsdMS, methylates adenine residues within a specific DNA sequence called the target recognition motif (TRM), as dictated by HsdS, while HsdR restricts unmethylated DNA. The various TRMs among type I RM systems represent bipartite and asymmetric sequences separated by a spacer of 6 to 8 random nucleotides (14). Similarly to S. aureus (10), we found that the hsdM and hsdR genes are fairly well conserved among S. epidermidis strains, while a particular hsdS gene appears to be conserved only within the same clonal complex, thus implying various specificities within the type I RM systems of S. epidermidis.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The basic modification complex, HsdMS, methylates adenine residues within a specific DNA sequence called the target recognition motif (TRM), as dictated by HsdS, while HsdR restricts unmethylated DNA. The various TRMs among type I RM systems represent bipartite and asymmetric sequences separated by a spacer of 6 to 8 random nucleotides (14). Similarly to S. aureus (10), we found that the hsdM and hsdR genes are fairly well conserved among S. epidermidis strains, while a particular hsdS gene appears to be conserved only within the same clonal complex, thus implying various specificities within the type I RM systems of S. epidermidis.…”
mentioning
confidence: 62%
“…Types I, II, and IV have been observed in both S. aureus (8)(9)(10)(11) and S. epidermidis (4,12,13); the type III system appears infrequently in both species. The type I RM system is the most diverse among different clonal types and consists of restriction, modification, and specificity units, designated HsdR, HsdM, and HsdS, respectively, assembled into multisubunit complexes (14,15). The basic modification complex, HsdMS, methylates adenine residues within a specific DNA sequence called the target recognition motif (TRM), as dictated by HsdS, while HsdR restricts unmethylated DNA.…”
mentioning
confidence: 99%
“…The type II systems consist solely of the methyltransferase-REase pair that is typically encoded within the same operon, although cases of apparent disjointed localization of the two genes have been reported (40). The most complex, ATP-dependent type I RM systems encompass three genes that encode the R (restriction), M (modification), and S (specificity) subunits of the RMS complex; the R subunit, in addition to REase, also contains a distinct ATPase domain that belongs to helicase superfamily II (15, 99, 163). Type III RM systems resemble type II systems in that they consist of only R and M subunits, but they are similar to type I systems in that the R subunit also contains the helicase domain and the reaction is ATP dependent (19, 136).…”
Section: Innate Immunitymentioning
confidence: 99%
“…For example, some Type I restriction enzymes methylate DNA using a site distinct from the site that hydrolyzes the DNA [42]. In many cases multifunctional enzymes are multisubunit complexes with the different catalytic activities distributed among the different subunits.…”
Section: Definitionsmentioning
confidence: 99%